Coupled techniques for arsenic speciation in food and drinking water: a review. Issue 1 (4th December 2014) - Sadee, Bashdar; Foulkes, M. E.; Hill, S. J.
Abstract : Arsenic is ubiquitous in nature appearing in various chemical forms. Abstract : Arsenic is ubiquitous in nature appearing in various chemical forms. The toxicity, environmental mobility and accumulation of As in living organisms depends on the form in which the element exists, thus requiring techniques which can identify specific forms whilst retaining their integrity during extraction and pre-treatment prior to measurement. Both organic and inorganic arsenic species may be present in food staples of both terrestrial and marine origin as well as natural waters, at sub ng l −1 to high mg l −1 levels. In this review, the speciation steps (sample preparation, species speciation and detection) most commonly used for the determination of As in food are described. High performance liquid chromatography separation with plasma source mass spectrometry is often the technique of choice due to its versatility, robustness and good detection limits. However, detection systems such as atomic absorption spectroscopy, atomic fluorescence spectrometry, and atomic emission spectrometry are also widely used and covered in this review together with some less utilised techniques.